2013
DOI: 10.1128/mbio.00810-13
|View full text |Cite
|
Sign up to set email alerts
|

Altered Dynamics of Candida albicans Phagocytosis by Macrophages and PMNs When Both Phagocyte Subsets Are Present

Abstract: An important first line of defense against Candida albicans infections is the killing of fungal cells by professional phagocytes of the innate immune system, such as polymorphonuclear cells (PMNs) and macrophages. In this study, we employed live-cell video microscopy coupled with dynamic image analysis tools to provide insights into the complexity of C. albicans phagocytosis when macrophages and PMNs were incubated with C. albicans alone and when both phagocyte subsets were present. When C. albicans cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 34 publications
5
62
0
Order By: Relevance
“…This difference is intriguing because engulfed white cells are able to survive within and then escape from macrophages in vitro (16)(17)(18). This in vitro result is compatible with the importance of macrophages in vivo for the early elimination of C. albicans (19,20) because macrophages which have engulfed C. albicans secrete immunoregulatory cytokines including interleukin-6 (IL-6), IL-1␤, IL-10, and tumor necrosis factor alpha (TNF-␣) (21) prior to the escape of C. albicans. These cytokines presumably promote the development and chemotactic migration of other innate immune cells, including neutrophils, which are more capable of killing C. albicans (22).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…This difference is intriguing because engulfed white cells are able to survive within and then escape from macrophages in vitro (16)(17)(18). This in vitro result is compatible with the importance of macrophages in vivo for the early elimination of C. albicans (19,20) because macrophages which have engulfed C. albicans secrete immunoregulatory cytokines including interleukin-6 (IL-6), IL-1␤, IL-10, and tumor necrosis factor alpha (TNF-␣) (21) prior to the escape of C. albicans. These cytokines presumably promote the development and chemotactic migration of other innate immune cells, including neutrophils, which are more capable of killing C. albicans (22).…”
supporting
confidence: 70%
“…White-cell supernatants of C. albicans, but not opaque-cell supernatants, stimulate chemotaxis of neutrophils (14). Since macrophages interact differently with opaque cells compared to white cells (15,20), we hypothesized that, like neutrophils, macrophages might display differential migration patterns toward white and opaque C. albicans. We first sought to determine whether C. albicans white-cell supernatants preferentially stimulate macrophage migration relative to the opaque-cell supernatants as assayed by a transwell cell migration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Co-culture of PMNs and macrophages showed that macrophages had higher ability of engulfing hyphae while PMNs played a predominant role in clearing yeast form C. albicans. 89 But when they were incubated separately, PMNs showed lower overall phagocytic capacity but higher susceptibility as compared with macrophages. 89 Taken together, it is hard to judge which phagocyte is more efficient for the lack of researches especially in vivo.…”
Section: Monocytes and Macrophagesmentioning
confidence: 99%
“…89 But when they were incubated separately, PMNs showed lower overall phagocytic capacity but higher susceptibility as compared with macrophages. 89 Taken together, it is hard to judge which phagocyte is more efficient for the lack of researches especially in vivo. New evidence also reveals that human macrophages may take up apoptotic neutrophils, so that they can own the antimicrobial peptides or acquire neutrophil granules to promote their antimicrobial activity.…”
Section: Monocytes and Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation